Global parental acceptance, attitudes, and knowledge regarding human papillomavirus vaccinations for their children: a systematic literature review and meta-analysis - Sophia Heyde; Vanesa Osmani; Gunther Schauberger; Claire Cooney; Stefanie J. Klug (BMC Women's Health)
Abstract Background This systematic literature review aims to summarize global research on parental acceptance, attitudes, and knowledge regarding human papillomavirus vaccinations. Methods The literature search was conducted in PubMed, Web of Science and Scopus, and included publications from 2006 to 2023. Study quality was assessed using the Newcastle-Ottawa Scale. The Grading of Recommendations Assessment, Development, and Evaluation guidelines were used to assess the strength of evidence for the primary outcome. Meta-analyses were performed using random-effects models to estimate pooled parental acceptance of HPV vaccinations. Studies were stratified by publication years, and a subgroup analysis was conducted to estimate vaccine acceptance rates by world regions. Additionally, sensitivity analyses examined the role of parents in accepting HPV vaccinations for children of different sexes. Results Based on 86 studies, we found that parents generally supported HPV vaccinations for their children, yet HPV vaccine acceptance rates showed high variation (12.0 to 97.5%). The subgroup analysis revealed geographical variations in pooled parental HPV vaccine acceptance rates, with the highest rate observed in Africa (79.6%; 95% CI: 73.5–85.2; I² = 98.3%; p < 0.01) and the lowest in North America (56.7%; 95% CI: 49.3–64.0; I² = 99.4%; p < 0.01). Sensitivity analyses showed that acceptance was higher for daughters than for sons, with mothers more willing to get their daughters vaccinated. The proportion of parents reporting barriers or benefits regarding HPV vaccinations varied widely (0.3 to 95.8%) between study regions. Across all world regions, fear of adverse effects and concerns about vaccine safety were the main barriers, whereas the desire to protect their children from cancer was a significant predictor of vaccine acceptance. Knowledge levels varied widely (6.5 to 100%) between world regions and according to the questions asked. In most studies, knowledge e.g., that HPV is sexually transmitted, and that HPV vaccination provides protection against cervical cancer, ranged from moderate to high. Conclusions The results indicated moderate parental acceptance of HPV vaccines. Public knowledge of HPV infection should be promoted, and special efforts should be made to minimize the existing barriers and increase vaccination accessibility and uptake.